EFFECT OF CONCENTRATE SUPPLEMENTATION ON PERFORMANCE OF ASSAM HILL DOES* - PATHAK, R.; SARMA, N. K.; BORA, M. C.; AHMED, H. F.; SAHARIA, K. K. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTAn experiment was conducted with 40 numbers of pregnant Assam Hill does in villageTetelia under Kamrup (Metro), Assam and the 40 does were randomly divided in two groupscomprising of 20 pregnant does in each group viz., G1 (Control group) where concentrateration was not supplemented and G2 (Experimental group) in which concentrate ration wassupplemented @ 200g/ head/ day from 91 days of pregnancy up to kidding (pre-partumperiod) and first month of lactation (post-partum period).The average initial body weight ofthe does during the pre-partum period under the control and experimental groups were16.28 ± 1.05 kg and 15.84 ± 0.60 kg respectively, while the final body weight of does were18.91 ± 1.09 kg and 18.99 ± 0.75 kg respectively. The average initial body weight of doesimmediately within 24 hours of kidding (post-partum) were 16.43 ± 1.03 kg and 16.21± 0.60kg respectively in control and experimental group while the final body weight of the doeswere 16.89 ± 0.99 kg and 16.74 ± 0.64 kg respectively after 1 month of lactation. Nosignificant difference was observed in body weight of the does during the pre-partum andpost-partum period in between the group. The total cumulative live weight gain during thepre-partum period were 2.63 ± 0.13 kg and 3.15 ± 0.23 kg respectively in control andexperimental group while during post-partum period the total cumulative live weight gainwere 0.46 ± 0.27 kg and 0.53 ± 0.08 kg respectively in control and experimental group.Key words: Assam Hill goat, Concentrate, Supplementation, Productive, Reproductive.